(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines the importance of modeling the processes of effective use of investment potential in ensuring the innovative development of the regional economy. In modern economic conditions, regions face increasing competition for investment resources, technological modernization, and sustainable economic growth. Therefore, the effective management of investment potential has become one of the key priorities of regional development policy. The study analyzes the theoretical foundations of investment potential, the relationship between innovation and regional economic growth, and the role of economic modeling in improving investment efficiency. Special attention is paid to the mechanisms of attracting investments, innovation infrastructure, and strategic planning. The article concludes that the use of modern economic models allows regional authorities to optimize investment flows, reduce risks, and strengthen innovative activity in various sectors of the economy.